Persepsi Mahasiswa terhadap Kurikulum Merdeka tentang Modul Ajar dan Profil Pancasila Ditinjau Berdasarkan Jenis Kelamin - Neindea Angelika; Ani Rusilowati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
There are still issues with interpretation regarding educators' attitudes regarding the implementation of the independent curriculum in educational units. Therefore, it's critical to understand how prospective teachers interpret the independent curriculum. The research's objective is to gain a thorough understanding of students' opinions regarding school fieldwork by analyzing and applying the autonomous curriculum from a gender perspective. This study employed a quantitative approach. methodologies for gathering data via interviews and questionnaires. Purposive sampling was the sampling strategy employed, taking into account students who attend schools that have adopted the independent curriculum. Thirteen samples total were used, and the practice sites were SMAN 1, SMAN 3, SMAN 5, and SMAN 6 in Semarang City. Statistical data and inferential data from precondition and hypothesis testing are analyzed. The study's findings, which had average scores of 74.58 and 71.02 in the good category, revealed that male and female students had different perspectives about the presence of teaching modules in the independent curriculum. Regarding the profile of strengthening Pancasila, male and female students' opinions are identical, with average scores in the good category being 66.15 and 66.98, respectively. As a result, it's critical to maximize the amount of time spent having in-depth conversations about the independent curriculum with aspiring teachers and current educators.